Mixed convection in the heated semi-circular lid-driven cavity for non-Newtonian power-law fluids: Effect of presence and shape of the block - Gangawane, Krunal M.; Öztop, Hakan Fehmi (Chemical Industry Press Co Ltd, 2020)
The present work delineates the hydrodynamics and thermal characteristics due to mixed convection in the lid-driven semi-circular cavity affected by the presence of the adiabatic block at its geometric center for two-dimensional. steady-state, laminar and for non-Newtonian power-law fluids. The semi-circular cavity has a diameter of D. The horizontal wall/lid is sliding with a uniform horizontal velocity (u = U) and is subjugated to the ambient thermal condition; while the curved surface is subjugated to a higher isothermal temperature. The convective characteristics inside the system is explored for the broad range of Richardson number (0.1 <= Ri <= 10), Prandtl number (1 <= Pr <= 100) and non-Newtonian power-law index (05 <= n <= 15) at a constant Grashof number of 10(4). Apart from this, the effect of shape (cross-section) of the inserted block, i.e., circular, square and triangular on heat transfer characteristics has also been explored. It is observed that the shear thickening fluids display better cooling characteristics. Besides, the cavity with immersed triangular block shows better heat transfer results than the circular and square blocks. The deviations observed in the flow and heat transfer characteristics in the cavity by inserting an adiabatic block as compared with cavity without block have been ascertained by calculating normalized Nusselt number (Nu(N)). The presence of the block was found to have a diminishing effect on the heat transfer due to convection in the cavity. In the end, the results of the study are summarized in the form of a predictive correlation exhibiting the functional dependence of average Nusselt number with Prandtl number, power-law index, and Richardson number. (C) 2020 The Chemical Industry and Engineering Society of China, and Chemical Industry Press Co., Ltd. All rights reserved.
Keywords: Heat transfer enhancement; Semi-circular cavity; Adiabatic block; Non-Newtonian fluids